Intermestic politics and the evolution of Nigerian foreign policy in the post-independence era - Demola, Ajijola Oladele (2023)
Internationally, state behaviour has long been acknowledged to be the result of a variety of factors originating both within the state and within its constituting external environment. These factors have widely different degrees of influence across states. Using Nigeria as an example, this study sought to determine whether Nigerian foreign policy is determined by internal or external factors. The framework of analysis used is neoclassical realism to capture the intersection of internal and external influences, namely, intermestic politics, in the formulation of Nigerian foreign policy. Following a review of the literature on foreign policy sources and a historical overview of Nigerian foreign policy, evidence of relevant sources in relation to Nigerian foreign policy was presented and Utilized to create a questionnaires, The Methodology utilized is mixedmethods sequential research design comprising both quantitative survey questionnaire and qualitative semi structure interview techniques. The evidence was then compared to the answers to the survey questionnaires and interview questions in the hopes of uncovering more information. The research findings from the quantitative hypotheses result collectively predicted that when it comes to Nigerian foreign policy, internal influences take precedence over external influences. Internal influences in the regard of Nigerian foreign policy have been found to be more pervasive than external influences,mas expected. This is not to say that external influences have been non-existent, but rather that internal considerations account for the majority of Nigerian foreign policy decisions. The findings from the qualitative interview reveal and corroborated to quantitative results as the majority of the interviewers elaborated that external factors are part of the foreign policy but not a determinant of a state’s foreign policy and Nigeria is not an exemption. Furthermore, the introduction of leadership personality and perception as a mediator shows positive impact on the relationship between external environment and foreign policy behaviour. Thus, this study recommends for the relevant stakeholders to formulate the policies that will enhance the internal and external environment to stimulate better foreign policy behaviour in and beyond Nigeria.